Be faithful: How to be faithful to the Word, your tasks, and the people who need you - Wiersbe, Warren W.; (1929-2019) (United Stated of America, 1988)
In a fast-paced, technology-based era when drive-thrus, cell phones, laptops, and Internet banking are the norm, it's sometimes hard to fathom that God doesn't appreciate our frail attempts at spiritual shortcuts.Through the pastoral epistles, 1 and 2 Timothy and Titus, with insight from Paul's letter to Philemon as well, Dr. Warren W. Wiersbe illustrates that working for God's Kingdom requires tenacity, never-ceasing prayer, and protective battle gear that only God can provide.
Keywords: Christian life -- Biblical teaching